Dynamic analysis of prestressed concrete sleepers (PCS) / Zulkarnain Ibrahim - Ibrahim, Zulkarnain (Faculty of Civil Engineering, 1995)
The nature of dynamic loading causes variations of pressure distribution between sleepers and ballast, hence it contributes to a wide range of bending moment. A train with a certain wheel load which runs at a certain speed imposes an external forces on the track. The means to withstand against this force is provided by the strength of track structure. The track structure forms a wheel running way, provide maintenance capacity and restoring the deformation and deterioration of the track. At higher speed, higher frequency sleeper stress component developed on quasi-static response due to dynamic force. This can lead to fairly high tensile stresses in sleepers and problems of concrete ties cracking. Thus analyses of dynamic load to prestressed concrete sleepers will be investigated under the positive bending moment test. This report is to analyse by aid of ANSYS on the structural behavior of the prestressed Concrete Sleepers when it subjected to dynamic load at the rail seat.